Jihad in Jammu and Kashmir: actors, agendas and expanding benchmarks. (3rd July 2016) - D'Souza, Shanthie Mariet; Routray, Bibhu Prasad
Abstract: Militant jihad as witnessed in Jammu and Kashmir (J&K) is centred around the primary objective of finding a separate homeland for the Muslims of the state. Opinion on whether this homeland would be an independent entity or merged into Pakistan remains inconclusive. And yet, this externally sponsored violent extremism, spearheaded by interlinked militant formations with significant local participation, has remained deeply religious, highlighting the alleged machinations of the Hindu Indians, both in the state and in India in general, against the Muslim population. Over the years, the objective of liberating Kashmir from Indian control has been attempted not just through an armed movement that targets the symbols of Indian state sovereignty within J&K, but has invested resources carrying violence into the Indian heartland and also making the movement transnational in character by aligning with global terror formations like the al Qaeda and the Islamic State. This paper is an examination of the shifting agenda as well as the activities of three primary militant formations operating in J&K: the Hizb-ul-Mujahideen, the Lashkar-e-Toiba and the Jaish-e-Mohammad and an assessment of the transformation of the Jihad that has bilateral, regional and international security implications.